Leveraging Urbanization in South Asia : Managing Spatial Transformation for Prosperity and Livability - Ellis, Peter; Roberts, Mark (Washington, DC: World Bank, 2015)
The number of people in South Asia's cities rose by 130 million between 2000 and 2011--more than the entire population of Japan. This was linked to an improvement in productivity and a reduction in the incidence of extreme poverty. But the region's cities have struggled to cope with the pressure of population growth on land, housing, infrastructure, basic services, and the environment. As a result, urbanization in South Asia remains underleveraged in its ability to deliver widespread improvements in both prosperity and livability.